2019
DOI: 10.3906/sag-1812-11
|View full text |Cite
|
Sign up to set email alerts
|

Can Apelin play a role in the etiology of tinnitus?

Abstract: Background and Aims: Tinnitus, which affects 15% of general populations and in 1-6%, the quality-of-life is seriously affected by a chronic condition. Chemical, oxidative, and emotional stressors are important in terms of the clinical course of tinnitus. Apelin mediates oxidative stress. We measured apelin levels in patients with tinnitus affecting both ears, but without hearing loss. Material and Methods: We enrolled patients diagnosed with bilateral idiopathic tinnitus. Tinnitus severity was determined usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
(24 reference statements)
0
6
0
Order By: Relevance
“…With regard to other parameters, previous studies that examined lipid levels in tinnitus patients found higher total cholesterol levels ( Martines et al, 2015 ; Avcı, 2021 ), higher LDL ( Avcı, 2021 ), lower HDL ( Ensari et al, 2019 ), and higher triglyceride levels ( Ensari et al, 2019 ; Avcı, 2021 ) in tinnitus patients compared to controls. In our sample, 35.9% had increased LDL and 5.1% decreased HDL cholesterol levels compared to reference values.…”
Section: Discussionmentioning
confidence: 95%
“…With regard to other parameters, previous studies that examined lipid levels in tinnitus patients found higher total cholesterol levels ( Martines et al, 2015 ; Avcı, 2021 ), higher LDL ( Avcı, 2021 ), lower HDL ( Ensari et al, 2019 ), and higher triglyceride levels ( Ensari et al, 2019 ; Avcı, 2021 ) in tinnitus patients compared to controls. In our sample, 35.9% had increased LDL and 5.1% decreased HDL cholesterol levels compared to reference values.…”
Section: Discussionmentioning
confidence: 95%
“…In a study that evaluated blood tests, intima media thickness (IMT) of the carotid artery, and the severity of tinnitus in patients with bilateral chronic subjective tinnitus with a prevalence of more than six months, Tinnitus handicapped index (THI) score, total cholesterol (TC), low-density lipoprotein (LDL), and hearing threshold were high in patients with tinnitus with high IMT [ 27 ]. In another study, tinnitus patients with normal hearing had lower mean blood HDL levels and higher TG levels than those of the control group [ 28 ]. In a study comparing patients with chronic subjective tinnitus, aged 18 to 70 years, with a control group to rule out the effects of aging, there was no difference in HDL levels between the two groups, but TC, TG, and LDL levels were high in the tinnitus group [ 29 ].…”
Section: Biomarkers In Chronic Subjective Tinnitusmentioning
confidence: 99%
“…Recently, research on apelin, which is derived from the vascular endothelium and adipocytes, showed that it prevents damage to blood vessels caused by oxidative stress in cardiovascular disease. In fact, since the apelin level of patients with tinnitus was low and decreased as the THI score increased, it is expected to be helpful in the treatment of tinnitus [ 28 ]. In conclusion, although the above results do not show the damaged site where oxidative stress occurs, oxidative stress is involved in the pathophysiology of tinnitus, similar to that observed in other diseases.…”
Section: Biomarkers In Chronic Subjective Tinnitusmentioning
confidence: 99%
“…To validate the RNA-seq results, RNA extracted from the 16 VS tissue samples was used for real-time RT-qPCR of eight genes of interest: PREX2 , APLNR , GFAP , PLVAP, and GPNMB, which were identified above, APLN because it is a ligand for APLNR [ 45 ] and because the plasma levels of APLN were reported to be negatively correlated with the severity of bilateral idiopathic tinnitus [ 46 ], KCNQ3 because this potassium channel is implicated in noise-induced tinnitus [ 47 ], and NLRP3 because NLRP3 inflammasome activation is implicated in VS-induced hearing loss [ 41 ]. All genes except PLVAP were detected with real-time RT-qPCR in both groups (tinnitus and no tinnitus).…”
Section: Resultsmentioning
confidence: 99%
“…Immunopositive apelin conglomerates did not overlap with macrophage/monocyte marker CD68-positive or Schwann cell marker S100-positive immunostaining on consecutive slides. Previous studies observed lower mean plasma levels of apelin in patients with tinnitus than in those without tinnitus [ 46 ]. Additionally, noise-exposed rats that were administered apelin-13 showed attenuated hearing loss compared to controls, which was hypothesized to be via sirtuin-1 regulation [ 76 ].…”
Section: Discussionmentioning
confidence: 99%